Characterization and Hydrogen Storage of Surface-Modified Multiwalled Carbon Nanotubes for Fuel Cell Application. (2nd October 2012) - Lin, Kuen-Song; Mai, Yao-Jen; Li, Shin-Rung; Shu, Chia-Wei; Wang, Chieh-Hung
Abstract : The synthesis, identification, and H2 storage of multiwalled carbon nanotubes (MWCNTs) have been investigated in the present work. MWCNTs were produced from the catalytic-assembly solvent (benzene)-thermal (solvothermal) route. Reduction of C6 Cl6 with metallic potassium was carried out in the presence of Co/Ni catalyst precursors at 503–623 K for 12 h. XRD patterns indicated that the abstraction of Cl from hexachlorobenzene and the formation of KCl precipitates were involved in the early stage of the synthesis process of MWCNTs. This result offers further explanation for the formation of MWCNT structure and yield using the solvothermal route depending on the Co/Ni catalyst precursors. The diameter of MWCNTs ranged between 30 and 100 nm and the H2 storage capacity of MWCNTs improved when 2.7–3.8 wt% Pd or NaAlH4 were doped. The XANES/EXAFS spectra revealed that the Co/Ni catalyst precursors of the MWCNT synthesis were in metallic form and Pd atoms possessed a Pd–Pd bond distance of 2.78 Å with a coordination number of 9.08. Ti-NaAlH4 or Pd nanoparticles were dispersed on MWCNTs and facilitated to improve the H2 storage capacity significantly with the surface modification process.